ATF6 Mediates a Pro‐Inflammatory Synergy Between ER Stress and TLR Activation in the Pathogenesis of Liver Ischemia‐Reperfusion Injury. Issue 7 (5th June 2014) - Rao, J.; Yue, S.; Fu, Y.; Zhu, J.; Wang, X.; Busuttil, R. W.; Kupiec‐Weglinski, J. W.; Lu, L.; Zhai, Y.
<x xml:space="preserve">Abstract</x> Although the roles of the metabolic stress in organ ischemia‐reperfusion injury (IRI) have been well recognized, the question of whether and how these stress responses regulate innate immune activation against IR remains unclear. In a murine liver partial warm ischemia mode, we showed that prolonged ischemia triggered endoplasmic reticulum (ER) stress response, particularly, the activating transcription factor 6 (ATF6) branch, in liver Kupffer cells (KCs) and altered their responsiveness against Toll‐like receptor (TLR) stimulation. Ischemia‐primed cells increased pro‐, but decreased anti‐, inflammatory cytokine productions. Alleviation of ER stress in vivo by small chemical chaperon 4‐phenylbutyrate or ATF6 small interfering RNA (siRNA) diminished the pro‐inflammatory priming effect of ischemia in KCs, leading to the inhibition of liver immune response against IR and protection of livers from IRI. In vitro, ATF6 siRNA abrogated the ER stress‐mediated pro‐inflammatory enhancement of macrophage TLR4 response, by restricting NF‐κB and restoring Akt activations. Thus, ischemia primes liver innate immune cells by ATF6‐mediated ER stress response. The IR‐induced metabolic stress and TLR activation function in synergy to activate tissue inflammatory immune response.